Work status, death anxiety and psychological distress during COVID-19 pandemic: Implications of the terror management theory. Issue 5 (28th May 2022) - Shakil, Muneeba; Ashraf, Farzana; Muazzam, Amina; Amjad, Maryam; Javed, Saba
Abstract: The present study determined the application of terror management theory during the COVID-19 pandemic in Pakistan. Death anxiety and psychological distress were examined in the context of work status. A sample of 478 from the general population voluntarily participated in the study. Findings revealed a significant moderating role of work status, illustrating the strong relationship between psychological distress and death anxiety for non-working participants. Therefore, psychological distress is related to more significant death anxiety among non-working than those who are working. This study highlights the importance of work as an anxiety buffering factor concerning mortality thoughts.